Improving skills in pediatric rheumatology in Colombia: a combined educational strategy supported by ILAR (2017)
Colombia is a densely populated country with a small number of pediatric rheumatology specialists, including 14 specialists for a population of 1,927,000 children in 2014. The objective of the study was to improve the skills required for early identification, timely referral, and management of musculoskeletal diseases, especially juvenile idiopathic arthritis (JIA), in a group of pediatricians and pediatric residents in a remote region of Colombia. Supported by grant programs developed by the International League of Associations for Rheumatology (ILAR), a combined educational strategy (blended learning) was implemented based on two classroom educational activities and four online modules. The students’ acquired knowledge and perception of the strategy were evaluated. Scores were reported as median values and interquartile ranges (IQR), and the differences between scores were estimated using the Wilcoxon test for equal medians. Forty-one students were enrolled, 37 completed the online modules, and 33 attended the final in-person session. The results of the written tests demonstrated an improved ability to solve clinical problems compared with the results of the tests before the course (the median initial vs. final test scores 3 (IQR = 1) vs. 5 (IQR = 0), p = 0.000). The students reported high levels of satisfaction related to compliance with the proposed objectives, the relevance of the contents and activities performed, and the impact on everyday practice. These types of strategies are useful as tools for continuing medical education. However, the results pertain only to short-term learning. It is necessary to evaluate their impact on “lifelong learning.”. © 2016, International League of Associations for Rheumatology (ILAR).